2018
DOI: 10.3775/jie.97.16
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and Air Pollution in the Persian (Arabian) Gulf States: Environmental Kuznets Curve Hypothesis

Abstract: This paper examines the relationship between economic growth (GDP per capita) and air pollution (CO2 emission per capita) in the Persian Gulf States based on the Environmental Kuznets Curve (EKC) hypothesis using regression analysis. First, the results provide weak support for the EKC hypothesis over the time series of data of 35 years from 1980 to 2014 spanning seven states. Instead, a positive linear relationship is suggested so that growth is associated with increasing emissions. Second, the factors underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This is an application of the theory of economic growth and income inequality postulated by Dr. Simon Kuznets, a Nobel laureate in Economics. The academic discussions on the EKC hypothesis have started in the 1990s by Grossman and Krueger (1991) and World Bank (1992), then, the discussions have extended from air pollutions to water contaminations and deforestation (Benoit et al, 2022;Csereklyei et al, 2017;Galeotti et al, 2009;Gopakumar et al, 2022;Markandya et al, 2006;Panayotou, 1997;Perman and Stern, 1999;Selden et al 1999;Sorgea and Neumann, 2020;Stern and Common 2001;Tsujimoto 2018 and. Especially, in the hypothesis, environmental impacts increase up to a certain level of economic growth and then start to decrease, showing an inverted U-shaped curve at the turning point.…”
Section: Definitionsmentioning
confidence: 99%
“…This is an application of the theory of economic growth and income inequality postulated by Dr. Simon Kuznets, a Nobel laureate in Economics. The academic discussions on the EKC hypothesis have started in the 1990s by Grossman and Krueger (1991) and World Bank (1992), then, the discussions have extended from air pollutions to water contaminations and deforestation (Benoit et al, 2022;Csereklyei et al, 2017;Galeotti et al, 2009;Gopakumar et al, 2022;Markandya et al, 2006;Panayotou, 1997;Perman and Stern, 1999;Selden et al 1999;Sorgea and Neumann, 2020;Stern and Common 2001;Tsujimoto 2018 and. Especially, in the hypothesis, environmental impacts increase up to a certain level of economic growth and then start to decrease, showing an inverted U-shaped curve at the turning point.…”
Section: Definitionsmentioning
confidence: 99%
“…In previous studies, the influence of socio-economic factors on atmospheric environment has been widely reported in different spatio-temporal scales. For example, the nonlinear relationship between economic growth and atmospheric environment is analyzed based on the Environmental Kuznets Curve [21,22]; Buehn, et al (2013) investigated the temporal and spatial variation of air quality across 122 countries in the past 20 years, and found that economic growth shows closely relation with air quality. The energy consumption and industrialization are important factors leading to deteriorated urban air quality, as they are accompanied with the emission of pollutants, especially the consumption of coal.…”
Section: Introductionmentioning
confidence: 99%
“…Energy use and transportation are main sources of air pollutants, which are closely related to the local patterns of social and economic development. Generally, the energy consumption is positively correlated with the level of regional economy, but the effect of energy consumption on air quality varies between regions [12][13][14]. In developed countries and regions, the wide use of cleaner fuels and proven technologies of cleaner production promotes the efficiency and reduces the emission of waste gas.…”
Section: Introductionmentioning
confidence: 99%